ANALISIS FAMA FRENCH FIVE FACTOR MODEL DAN THREE FACTOR MODEL DALAM MENJELASKAN RETURN PORTOFOLIO SAHAM YANG MASUK PADA INDEKS KOMPAS 100 PERIODE 2010-2015 - Sheila Citra Wijaya; Werner Ria Murhadi; Mudji Utami (CALYPTRA, 2017)
Abstract - This study aims to test the Fama French Five Favtor Model (5FF) and Three Factor Model (3FF) in explaining cross sectional returns on stocks which entered Kompas 100 Index period 2010-2015. Factors in the model are market risk, size, book-to-market equity, profitability, dan investment. This study uses a quantitative approach with multiple linear regression analysis in the form of panel data for overall portfolio and also for each portfolio that has been made. The findings of this study indicate; market risk and profitability significant positive effect on returns. Size and investment has significant negative effect to return.Meanwhile, the B/M factor effect is insignificant to return. This study also find that The 5FF model perform better in explaining cross sectional returns than 3FF model. Keywords: Fama and French Five Factor Model, Fama and French Three Factor Model, Size, Value, Profitability, Investment